(untitled) (The Pakistan Development Review, 2015)
Aslam-o-alaeekum! Thank you very much for coming. I would like to welcome you all to the Conference and hope it would be of benefit to us, not just academically and intellectually but that it would be of benefit to billions of people on earth who are living in abject poverty. One of the important things to realise is that this is not inevitable but rather is a result of the choices we have made. What are these wrong choices and how can they be changed is the theme of this Conference. One of the things I would like to say is that world is a battle place of ideas and these are being played out on a large scale. In the start of the 20th century, growth was understood as the process of capital accumulation. Marx and Keynes and classical economists agree on this idea that growth is about getting more wealth. However, this idea has fallen into disrepute and the clear conclusion is that growth is about development of human capabilities. It is a multidimensional process. It has many components and just the accumulation of wealth is not the solution to the problems we face. Again, it was thought that development was about gaining technology and building industries but I think the realisation is growing stronger that it is all about human lives.